Women's Language Features In Female Characters The Secret Of Moonacre Movie: A Sociolinguistic Study - Indah Puspita Mahdiyah; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2026)
This research explores the relationship between language functions and women's language features in conversations among female characters in the film The Secret of Moonacre. Using a qualitative content analysis of transcripts, it applies Lakoff’s model of women’s language and Jakobson’s language functions (as cited in Juanda, 2022). Seven features of women’s language were identified and quantified: lexical hedges (23%), rising intonation on declaratives (13%), superpolite forms (16%), empty adjectives (13%), tag questions (10%), avoidance of strong swear words (13%), and emphatic stress (10%). The results indicate that these linguistic features and functions play a significant role in shaping interpersonal relationships; appropriate word choice and function use can enhance conversational effectiveness and strengthen social bonds. The study contributes to sociolinguistics by showing how women’s language characteristics and language functions interrelate in film dialogue, offering insights into gendered communication in mediated contexts.